BURNOUT DI KALANGAN PENDAKWAH - Salama, Nadiatus (Da'wa and Communication Faculty State Islamic University Walisongo, Semarang, Indonesia, 2014)
Burnout is a phenomenon that arose from a great expectation to do the best for other people. But when the relationship is